"This Unpopular Art": The Role of the Urban Poet in the Writings of W.H.Auden. - Saint, David Antony (My University, 1992)
This study is an analysis of the complex presentation of the city motif, with its vast range of cultural" and psychological connotations, in the poetry and prose of W.H.Auden (1907 - 1973), leading to the troubling question for the poet of his role in this environment, a subject which significantly pre-occupied him throughout his career. The thesis also follows the parallel development of Auden's poetic style from his "Poems" of 1930, through to the highly distinctive verse of his maturity, showing the relationship between altering form and altering content across that time.
[missing page :30]
Keywords: English Language and Literature; English Language and Literature